Research progress on rolling contact fatigue damage of bainitic rail steel. (January 2023) - Ruijie, Zhang; Chunlei, Zheng; Bo, Lv; Xubiao, Wang; Xiaofeng, Li; Yanguo, Li; Fucheng, Zhang
Highlights: This paper summarizes the latest research results of domestic and foreign data. This paper introduces the influence of various factors on track damage in detail. The measures to prolong the track life are put forward. The future research on rolling contact fatigue damage is prospected. Abstract: In recent years, with the continuous improvement of train carrying capacity and speed, more strict requirements are put forward for the service performance of rail steel. Bainitic steel has been widely recognized by researchers for its excellent comprehensive performance, and has been gradually applied in field of wheel/rail contact. However, there are still many damage problems in the actual service process of bainitic steel for rail, one of the main damage forms is rolling contact fatigue damage. Therefore, the failure modes and mechanisms of rolling contact fatigue have been studied by many scholars at home and abroad. The existing research results show that there are many factors affecting the rolling contact fatigue damage of bainitic rail steel. There are many failure mechanisms and the coupling relationship between the factors causing the damage is not clear, and the research results of restriction relationship between the factors have not been fully applied to the protection of rail steel. Especially, the damage mechanism analysis of new rail steel under complex working conditions is still in the initial stage and lacks comprehensive research results. Based on a large number of domestic and foreign data, combined with the failure forms and characteristics of rail steel, this paper summarizes the latest research results on the contact fatigue damage of bainitic rail steel in recent years from the aspects of steel quality, service conditions, medium and other factors. The main factors affecting rail contact fatigue damage and measures to prolong the rail life are put forward, and the future research on rolling contact fatigue damage is prospected.